Activist framing of abortion and use for policy change in Peru. Issue 1 (1st January 2019) - Beavin, Cynthia; Billings, Deborah L; Chávez, Susana
Abstract: Identifying how activists frame the topic of abortion is key to unpacking their understanding of "abortion" in Peru. It is important to explore how and why certain frames are privileged in attempts to shift policy and social norms. In 2016, the authors conducted qualitative interviews with 10 activists in Lima, Peru to develop a deep understanding of these issues. Activists worked through different approaches and lenses, including law, medicine, sociology, psychiatry, journalism, non-governmental organisational management, LGBTQ rights, and indigenous rights. Four common frames emerged through the analysis and those frames shifted based on whether activists were speaking to the general public or to policymakers. Understanding Peru's activist framing of abortion can contribute to a deeper analysis of regional and global movements to legalise abortion, which also take into account local specificities.